Mejora aplicada en el área de producto de una agencia de viajes - Rodriguez Vaca, Sebastian (2021)
The objective of this research was the business improvement of a travel agency, specifically in its product area. This was possible from a descriptive case study oriented to propositional action that generates value as academic research and as an improvement proposal for the company. For this, techniques and tools from industrial engineering and related areas were used.